The use of complementary and alternative drugs by cancer patients. - Herdeiro, Maria Teresa (2016)
The use of complementary and alternative medicnes has been enlarging worldwide and has been increasing. This study sought to review information avalable in order to identify the medicinal plants most used by cancer patients.